RELIGIOUS MODERATION IN ART: A COMPARATIVE STUDY BETWEEN SURAKARTA AND CAIRO - Unik Dian Cahyawati; Aditya Eko Adrianto; Wahid Tuftazani Rizqi; Muhammad Syadidul Isytiher (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study explores the perceptions of art students in Surakarta regarding religious moderation in artistic expression and compares them with the context in Cairo through a literature review. The research employs a qualitative method with a literature-based approach and thematic analysis techniques. The analysis integrates Talcott Parsons' AGIL theory (adaptation, goal attainment, integration, and latency) and Dahrendorf's conflict theory to examine the tension between freedom of expression and social norms. Religious elements in art often spark controversy, especially in culturally diverse regions like Surakarta. The study aims to understand how future artists view and incorporate religious values into their work. Participants were purposively selected, considering religious diversity and artistic experience. Findings reveal that art students in Surakarta view religious moderation as an effort to create harmony in art, despite challenges in balancing religious values and creative freedom. Using AGIL theory, the study identifies students' adaptation to religious values, their goal to produce inclusive art, integration of artistic freedom with religious norms, and the latency of internalizing moderation values. Meanwhile, Dahrendorf's conflict theory highlights social tensions influencing students' creative processes. The literature review on Cairo underscores religious moderation as a foundation for social harmony, with Al-Azhar University exemplifying tolerance through religious education. This research contributes to the academic field by offering deeper insights into the relationship between art, religion, and religious moderation. It provides practical guidance for art institutions to develop inclusive and harmonious art practices in diverse cultural and religious contexts.